Faktor-faktor yang Mempengaruhi Kinerja Pegawai Perumahan Rakyat, Kawasan Pemukiman dan Cipta Karya - Novia Dia Kumala; Ertien Rining Nawangsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study has the goal of knowing and analyzing the effect of personal factors, leadership factors, team factors, system factors, contextual/situational factors on employee performance as well as to determine the most dominant factors influencing the performance of employees of the PRKP & Cipta Karya Office of East Java Province. Data collection was carried out using a questionnaire method with a sample of 62 respondents. This research uses quantitative research methods. The data analysis technique used is the PLS approach (Partial Least Square) with a software tool in the form of SmartPLS Version 3. The results of the study show that: 1)Personal Factors has a positive and significant effect on the performance of the PRKP and Cipta Karya Offices of East Java Province, 2)Leadership Factors has a positive and significant effect on the Performance of Employees of the PRKP and Cipta Karya Offices of East Java Province, 3)Team Factors does not affect the Performance of the East Java Province PRKP and Cipta Karya Office Employees, 4)System Factors does not affect the Performance of the East Java Province PRKP and Cipta Karya Office Employees, 5)Contextual Factors has a positive and significant effect on the Performance of Employees of the PRKP and Cipta Karya Offices of East Java Province.